Freund´s complete adjuvant effect on BALB/c mice: an insight into inflammation and oxidative stress after immunity challenge - Pohanka Miroslav; Voborníková Irena; Fusek Josef (My University, 2016)
Freund´s complete adjuvant (FCA) is a mean used for improving immunization efficacy in experiments and veterinary medicine. Despite high efficacy, it is not used in human vaccination due to number of adverse effects. Arthritis can be an example of a typical adverse consequence. In this work, we decided to investigate the link between oxidative stress and inflammation in animals exposed to FCA. BALB/c mice received either saline or FCA in doses 10-50 µl and were euthanized from one to three days after infection. Interleukins (IL) IL-2, IL-4 and tumor necrosis factor α (TNF-α) were determined in plasma. Ferric reducing antioxidant power (FRAP), malondialdehyde by thiobarbituric acid reactive substances assay (TBARS), reduced glutathione (GSH) and caspase-3 were measured in livers, muscles and other organs. We determined significant effect of FCA on TBARS and GSH in the livers. Beside this, TBARS were altered in muscles as well. Inflammation was confirmed by increased level of TNF-α. Taking the results into account, we infer that the harmful effect of FCA is mediated not only by inflammation but also by oxidative. This should be considered when pathological consequences of FCA are scored (Fig. 4, Ref. 21).
Účinek Freundova kompletního adjuvantu u BALB/c myší: ozřejmění zánětu a oxidativního stresu po imunitní výzvě
Keywords: adjuvant; arthritis.; immunity; inflammation; glutathione; oxidative stress; vaccination; adjuvant; oxidativní stres; zánět; glutathion; imunita; vakcinace; artritida